Evaluating assessment practices in English programs: A study at Islamic higher education - Chamisah, Chamisah; Ridhwan M Daud (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study examines the landscape of language assessment approaches within undergraduate English Education programs at Islamic higher education institutions. Employing a descriptive qualitative methodology grounded in a systematic literature-based analysis, the research outlines predominant trends, persistent challenges, and emergent opportunities in contemporary assessment practices. The findings indicate a continued dominance of traditional, summative assessment models, which persists despite national policy initiatives advocating for a paradigm shift toward formative, authentic, and technology-enhanced evaluation. Significant impediments to the adoption of these innovative approaches are identified, encompassing limited instructor assessment literacy, insufficient institutional support structures, and inadequate technological infrastructure. Conversely, the analysis notes a growing recognition of the potential inherent in digital assessment tools to transform pedagogical evaluation. In conclusion, the study proposes strategic recommendations, including targeted professional development for educators, systematic curricular reform, and the strategic integration of educational technology. These measures are suggested as essential for aligning assessment frameworks with the principles of communicative language teaching and the exigencies of 21st-century education. The implications of this research emphasize the necessity for systemic, context-sensitive reform to develop assessment models that more effectively foster language acquisition in the unique milieu of Islamic higher education.